Modelos de negócio no campo da educação profissional em cursos livres: um estudo a partir do tripé de criação, configuração e apropriação do valor - Silva, Tiago Leite da (2020)
The lack of skilled labor has mainly put pressure on professional education that has expanded as a result of federal, state and municipal governments, as well as private enterprise. The main objective of professional education is to promote courses that facilitate the insertion of students in the job market. However, there are worrying data regards professional education. Firstly, there are a third of alumni who have not been able to gain a job placement in the area they have qualified in the past. And secondly, there is a suppressed demand for professional education courses due to lack of student´s financial resources and also for the lack of courses, especially in the less developed regions of the country. Therefore, understanding the structure of the business model in the professional open courses segment an becomes a relevant topic of interest. Thus, this research aims to understand how strategies of creation, configuration and appropriation of value in the context of professional education. Value is created by discovering and recognizing opportunities by analyzing the entire business ecosystem, combining the resources and capabilities of the company (or School) to deliver more value to all customers and stakeholders. But how does this "discovery and recognition of opportunities" take place? What is the role of multiple agents in the value creation? To answer these questions, a qualitative research was conducted, using the interpretative paradigm and characterized by being exploratory and descriptive for three dimensions of the value cycle (creation, configuration and appropriation). As result, the survey shows that schools offering professional courses need a flexible organizational structure and communication speed in regards of market demand, customer perception of value, etc.; Rapidly put courses in the market with high demand; Focus on students placement in the job market; Have pricing policies according to student context (generally, students without income or employment with a strong tendency to make a purchase decision after price comparison) and deeply develop and explore partnerships (commercial, pedagogical and for jobs).